Utilization of palm olein by Pseudomonas aeruginosa for rhamnolipids production - Azrul Arif Mohd Said (2015)
Rhamnolipids are amphiphilic organic surfactant compounds produced by microorganisms as secondary metabolites and able to replace synthetic surfactants. In this study, Pseudomonas aeruginosa was used for the production of rhamnolipids using mineral salt medium (MSM) broth with carbon sources, 1% Palm olein and or with the combination of 1% glucose and 1% Palm olein (simultaneous/ log phase added) at pH 7 and 30°C with 180 rpm-shaking for 7 days. The concentration of rhamnolipids production and rhamnolipids stability were determined by optical density method, orcinol analysis, oil spreading technique and emulsification index (E24%) respectively. For the growth of cell all samples reached stationary phase after 96 hours along with the highest production of biosurfactant. The rhamnolipids have been determined as rhamnose content and the yields were 0.733±0.0447, 0.827±0.0169, 2.160±0.0335 and 2.288±0.0142 g/L for glucose only, Palm olein only, Palm olein (simultaneously phase) and Palm olein (log phase) respectively. For the percentages of E24%, all samples show higher emulsification index (52 to 58%) and good result for the oil spreading technique (5.3 to 7.5 cm). In thermo-stability test, good stability was obtained when submitted at 4°C to 120°C (regarding emulsification capacity of diesel and kerosene). This study show that Pseudomonasaeruginosa has the ability to degrade hydrocarbon and the production of rhamnolipids was higher with the combination carbon sources rather than single carbon source.